A Safety Message Broadcast Strategy in Hybrid Vehicular Network Environment. (10th August 2017) - Feng, Dan; Yajie, Ma; Fengxing, Zhou; Xiaomao, Wang; Kai, He
Abstract: As the Vehicle to Vehicle or Vehicle to Infrastructure communication in Vehicular Ad Hoc Network (VANET) is usually based on opportunity network, the transmission delay will be high with the low vehicle density or far transmission distance. As the result, the Quality of Service requirements of safety message dissemination cannot be satisfied. The paper proposed a safety message broadcast strategy based on VANET-cellular architecture, and it does not rely too much on traffic density or additional deployment of Road Side Unit. Meanwhile, the only relay node is selected from the candidate relay node subset via the acknowledgement mechanism of short control packet. The strategy can solve the problem of competitive channel and redundant data in VANET.